2008
DOI: 10.1557/jmr.2008.0232
|View full text |Cite
|
Sign up to set email alerts
|

Berkovich indentation of diamondlike carbon coatings on silicon substrates

Abstract: The deformation behavior of diamondlike carbon (DLC) coatings on silicon substrates induced by Berkovich indentation has been investigated. DLC coatings deposited by a plasma-assisted chemical vapor deposition technique were subjected to nanoindentation with a Berkovich indenter over a range of maximum loads from 100 to 300 mN. Distinct pop-ins were observed for loads greater than 150 mN. However, no pop-out was observed for the loads studied. The top surface of the indents showed annular cracks with associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Investigation of the data reported in XTEM studies by Haq and co-workers clearly shows that the influence of indenter geometry is greater than that of coating thickness [38][39][40][41]. In the micro-scratch test the indenter radius was 25 m so compressive strain in the coating should be minimal.…”
Section: Deformation Mechanism In the Scratch Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the data reported in XTEM studies by Haq and co-workers clearly shows that the influence of indenter geometry is greater than that of coating thickness [38][39][40][41]. In the micro-scratch test the indenter radius was 25 m so compressive strain in the coating should be minimal.…”
Section: Deformation Mechanism In the Scratch Testmentioning
confidence: 99%
“…m spherical indenter the localised compressive plastic strain determined by cross-sectional transmission electron microscopic analysis (XTEM) is relatively low (~4%) compared to that induced by Berkovich indentation to the same load [38]. Investigation of the data reported in XTEM studies by Haq and co-workers clearly shows that the influence of indenter geometry is greater than that of coating thickness [38][39][40][41].…”
Section: Deformation Mechanism In the Scratch Testmentioning
confidence: 99%
“…Also evident in the P-h curves are steps or discontinuities during loading (pop-ins) and unloading (pop-outs), both in coated and uncoated samples. Pop-ins and pop-outs in brittle materials are typically related to fracture events [18][19][20][21][27][28][29] or to phase transformations in the case of silicon. 30,31 The number of pop-ins in coated systems seems to be higher than in the uncoated substrate, and also to increase with increasing film thickness.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental procedure used for deposition of the coating, nanoindentation studies, and the characterization of the coatings following indentation has been discussed in detail in earlier publications. [20][21][22][23] A. Parameters for simulation…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18][19] Cross-sectional transmission electron microscopy (XTEM) studies of diamondlike carbon (DLC) coatings on silicon substrates [20][21][22][23] have shown that the presence of the coating alters the deformation behavior in the substrate so that, at lower loads of indentation, only slip is observed in the substrate, without any phase transformation being evident. Therefore, in such systems the initial deformation mechanism responsible for pop-ins changes from phase transformation to dislocation nucleation in the silicon substrate.…”
Section: Introductionmentioning
confidence: 99%